Evaluating the SAVA System as a Digital-Based Quality Strategy in Islamic Schools: A CIPP Model Approach - Hisyam, Muh; Hasan, Mardhiah (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2025)
This study evaluates the implementation of the SAVA system as a digital-based quality management strategy at SDIT Ar-Rahmah, Indonesia, using the CIPP (Context, Input, Process, Product) evaluation model. The research was conducted through a qualitative descriptive approach, employing interviews, observations, and documentation, with data analysis following Miles and Huberman’s interactive model. The findings reveal that the SAVA system was adopted in response to contextual needs for systematic monitoring of academic and affective services. In terms of input, teacher training, adequate infrastructure, and strong parental involvement provided the foundation for implementation. The process dimension highlighted comprehensive academic strategies including teacher training, supervision, use of digital media, and project-based assessments alongside affective strategies such as daily Islamic practices, character-building programs, and social activities, all integrated into the SAVA system. The product dimension demonstrated measurable impacts: efficiency in report preparation, increased student motivation, and observable improvements in honesty, discipline, and cooperation. Despite these achievements, challenges remain, particularly the absence of a mobile version and the need for automatic notifications. Theoretically, this study contributes to the literature on educational quality management by showing how digital innovation can be systematically combined with values-based education in Islamic schools. Practically, it offers a best-practice model for holistic quality assurance, integrating academic excellence with character development through data-driven strategies.